2022
DOI: 10.1108/ijefm-02-2021-0009
|View full text |Cite
|
Sign up to set email alerts
|

Examining antecedents of residents’ support for the European Capital of Culture project – event’s sustainability perception, emotional solidarity, community attachment and brand trust

Abstract: PurposeThe primary purpose of this paper is to investigate the effects on support for the European Capital of Culture (ECoC) project development of residents’ perception of the project’s sustainability, emotional solidarity toward tourists, community attachment and brand trust.Design/methodology/approachSurvey research was conducted among 303 residents of Novi Sad, which has been selected to be the ECoC for the year 2022.FindingsThe findings confirmed the positive roles of three aspects of the event’s sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 70 publications
0
4
0
1
Order By: Relevance
“…Emotional solidarity is a notion that forges a collective emotion based on shared assumptions within the luxury dining context, aligning with the emotional values of the customers (Batat, 2022a). Emotional solidarity is perceived as a set of affective credentials, deeply ingrained in a commonly held value system that subsequently influences consumers' ethical biases, particularly with regard to community and social benefits (Chua et al, 2022;Sagovnovi c et al, 2022). In particular, the emotional solidarity framework veers away from the traditional "self-versus-other" dichotomy, emphasizing the "feeling of togetherness" in the considerations of luxury dining (Juric et al, 2021).…”
Section: Emotional Solidarity In Luxury Foodservicementioning
confidence: 99%
See 1 more Smart Citation
“…Emotional solidarity is a notion that forges a collective emotion based on shared assumptions within the luxury dining context, aligning with the emotional values of the customers (Batat, 2022a). Emotional solidarity is perceived as a set of affective credentials, deeply ingrained in a commonly held value system that subsequently influences consumers' ethical biases, particularly with regard to community and social benefits (Chua et al, 2022;Sagovnovi c et al, 2022). In particular, the emotional solidarity framework veers away from the traditional "self-versus-other" dichotomy, emphasizing the "feeling of togetherness" in the considerations of luxury dining (Juric et al, 2021).…”
Section: Emotional Solidarity In Luxury Foodservicementioning
confidence: 99%
“…From this perspective, solidarity became an inherent term in the realm of human rights; people needed universal recognition to mirror their self-esteem and self-affirmed behaviors (Laitinen et al ., 2014). Solidarity represents a commitment to undertake financial, social, and emotional burdens to assist others whenever individuals recognize similarity in a relevant mechanism of human civic virtue (Šagovnović et al ., 2022). The value of civic virtue and the status of a person’s moral core could reveal the deontic status of individuals and relations of recognition or, in terms of moral solidarity (Laitinen et al ., 2014).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Academics have also tried to introduce community trust into the study of performance perceptions [23,24]. Researchers have generally concluded that community trust has a positive effect on performance perceptions, and that residents in areas with higher levels of community trust are better able to perceive local governance performance [25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Az EKF cím hozzájárul a márkaépítéshez és a város láthatóságához, mivel maga a cím egy felismerhető márkát képvisel (KOVAČIĆ et al 2021, ŠAGOVNOVIĆ et al 2022…”
Section: Forrás: Saját Szerkesztés Jászberényi (2014) Jászberényi (20...unclassified